Acute Sleep Loss Upregulates the Synaptic Scaffolding Protein, Homer1a, in Non-canonical Sleep/Wake Brain Regions, Claustrum, Piriform and Cingulate Cortices - Zhu, Jingxu; Hafycz, Jennifer; Keenan, Brendan T.; Guo, Xiaofeng; Pack, Allan; Naidoo, Nirinjini (Frontiers in Neuroscience, 2020)
Homer proteins are a component of the post-synaptic density of neurons that are necessary for the maintenance and consolidation of behavioral state. The dominant negative protein homer1a is rapidly increased by neuronal activity and sleep loss. Homer1a knockout mice with globally absent homer1a have reduced ability to sustain wakefulness during the active period. It is not known whether homer1a is required globally or in very specific brain regions or neurons for its role in maintaining wake. In this study, we examined the expression of homer1a, an immediate early gene involved in intracellular signaling cascades, in mice subjected to extended wakefulness. We found that mice displayed increased expression of homer1a in the claustrum, a brain region thought to be involved in consciousness, as well as the cingulate and piriform cortices compared to non-sleep deprived mice. In situ hybridization (ISH) studies also indicate that homer1a is not induced in the known wake promoting regions with sleep deprivation, but is instead upregulated primarily in the claustrum and piriform cortex. Examination of homer1a expression levels with recovery sleep after sleep deprivation indicate that baseline homer1a expression levels were restored. Further, we have identified that homer1a is upregulated in excitatory neurons of the claustrum suggesting that homer1a promotes wakefulness through activating excitatory neurons. This work identifies regions previously unknown to be involved in sleep regulation that respond to acute sleep deprivation or enhanced waking.